Calcareous plankton biostratigraphy of the Miocene sediments of the Tremiti Islands (Southern Italy) - IACCARINO S.; FORESI, LUCA MARIA; MAZZEI, ROBERTO; SALVATORINI, GIANFRANCO (2001)
An integrated biostratigraphic study based on calcareous plankton (calcareous nannofossils and planktonic foraminifera) from ten sections revealed that the Neogene sedimentary succession of the Tremiti Islands encompasses a stratigraphic interval from the latest Burdigalian (?) - Langhian up to the early Messinian. However, clear signals of condensed sedimentation are recognisable both at the base and the top of the sequence on the basis of biostratigraphic evidences and on large amounts of glauconite grains. The biostratigraphic results indicate that the sedimentary evolution of the Tremiti Islands is characterized by a trangressive-deepening-regressive trend which culminated with the emersion of the islands in the early Messinian (at about 6 MA). This trend follows the evolution model outlined for the Salento peninsula and the Puglia offshore.